Influence of Teachers’ Behavior on students’ Academic Achievement at University Level - Munir, Dr. Hina; Dr. Afrina Afzal; Rahima Arshad (Journal of Arts & Social Sciences, 2020)
The aim of this study was to explore influence of teachers’ behavior on students’ academic achievement at university level. Researcher applied quantitative research method and used simple random sampling technique. Questionnaire were administered among sample of 387 students of social sciences departments of different universities. Collected data were analyzed applying Descriptive statistics and inferential statistics. Results of the study showed that all the factors (Classroom Activities, Rules, routine & support, concerned behavior and Negative Behavior) of teachers’ behavior are highly correlated with each other and with the students’ academic achievement but there was also a positive but weak relationship between two factors Rules routine & support and Negative Behavior. This study concluded that the majority of students were found to be satisfied with the positive behavior of their teachers. The results of the study also showed that there is a significant correlation between the teachers’ behavior and students’ academic achievement.